Professionals and Children with Vision and Multiple Disabilities or Deafblindness: Contemporary Challenges and Recommendations - Παπαζαφείρη Μαρία; Αργυρόπουλος Βασίλειος (Education Sciences, 2021)
The present study aims to describe the profile of professionals who are engaged in educational and therapeutic interventions regarding children with vision and multiple disabilities or deafblindness. In addition, the study focuses on aspects of educational environment and usage of educational materials and communication methods regarding this population. Forty-six professionals who were working in various educational settings in Greece, within which children with vision and multiple disabilities were enrolled, participated in this study. Data were obtained through semi-structured interviews. The findings highlighted the lack of professionals’ training and experience into the field of multiple disabilities with vision impairment or deafblindness. Finally, the results may constitute an added value to the enrichment of existing training programs or to the construction of new evidence-based training programs regarding students with multiple disabilities with vision impairment or deafblindness.